2009
DOI: 10.1063/1.3086632
|View full text |Cite
|
Sign up to set email alerts
|

Mean field theory of ionic free energy using scaled binding energies

Abstract: A mean field model for ionic free energy is developed using the scaled binding energy formula. The model is evaluated using experimental data on Hugoniot, phase diagrams, melting curves, and other thermodynamic parameters of several solids. Predictions of the model are also compared with the Debye–Gruneisen theory, which is also based on the same binding energy formula. The binding energy formulation employs just four parameters, all corresponding to ambient condition—density, bulk modulus, its pressure deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Recently, Bhattacharya and Menon [14] have demonstrated that λ in Eq. 1 may be treated as an adjustable parameter, and for the case of aluminum, its value is −2.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Recently, Bhattacharya and Menon [14] have demonstrated that λ in Eq. 1 may be treated as an adjustable parameter, and for the case of aluminum, its value is −2.…”
Section: Resultsmentioning
confidence: 98%
“…These studies clearly reveal that the parameter t or λ, which in turn determines the Grüneisen parameter, should be treated as a free parameter as long as its choice gives a better thermal description for a given material. Illustrating this fact, Bhattacharya and Menon [14] have examined this point within the MFP formalism, and have proposed that for the case of fcc-Al, either λ = −2 or t = −1 value gives correct thermophysical properties at high temperatures. While for other metals, they retain the value of λ as either −1 or +1.…”
Section: Choice Of Parameter λ In Mfpmentioning
confidence: 92%
See 3 more Smart Citations